An Unusual Case of Denervation Changes of the Intercostal Muscles Associated with Intercostal Neuralgia in a Patient with Chest Pain - Botchu, Rajesh; Aspland, Lorraine; Ariyaratne, Sisith; Burgess, James; Bhogal, Gurjit; Beale, David (Acta medica Lituanica, 2024)
Musculoskeletal aetiologies account for most patients presenting with chest pain. Intercostal neuralgia is a lesser-known cause of musculoskeletal chest pain, which can present a diagnostic challenge with nonspecific imaging findings. We report a case of a 31-year-old male who presented with severe lower thoracic and chest wall pain following a suspected viral infection, where Magnetic Resonance Imaging (MRI) revealed characteristic features of denervation oedema within the affected intercostal muscles. This pattern of imaging findings in intercostal neuralgia is sparely described in the current literature. MRI along with history and examination was crucial in diagnosing the condition and excluding other potential causes of musculoskeletal chest wall pain on this occasion. The patient’s symptoms were subsequently managed conservatively. The case highlights the importance of considering intercostal neuralgia as a potential cause of chest wall pain, particularly in the setting of post viral infection and absence of preceding mechanical musculoskeletal injury and explores an uncommon yet characteristic imaging finding which may be important in diagnosing the condition.
Keywords: Denervation; post viral infection; intercostal neuralgia; rib pain; thoracic; MRI